PENERAPAN MODEL DISCOVERY LEARNING PADA MATA PELAJARAN IPS UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV SEKOLAH DASAR - Fatiya Auliya; Rafiqa Dzurriyya; Catharina Indah Kartika; Hana Naina; Priyono Tri Febrianto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Social Studies (IPS) learning at the elementary school level has a crucial role in instilling character and developing students’ critical thinking skills, in line with the fourth goal of the Sustainable Development Goals (SDGs). However, low learning outcomes are often caused by teaching approaches that lack innovation and are not relevant to real-life contexts. This study examines the implementation of the discovery learning model to improve Social Studies learning outcomes, particularly on the topic of landform classification and its relation to professions in fourth-grade elementary school students. The method used is a literature review of relevant scientific articles published between 2022 and 2025. The results show that the implementation of the discovery learning model, supported by interactive multimedia, illustrated student worksheets (LKPD), and e-modules, significantly improves students’ conceptual understanding and learning outcomes. Through independent exploration, students are able to identify the relationship between geographical conditions and community economic activities in a meaningful way. Therefore, the discovery learning model is an effective strategy to support high-quality Social Studies learning that is relevant to the demands of 21st-century education.